High expression of LASS2 is associated with unfavorable prognosis in patients with ovarian cancer. Issue 8 (7th December 2018) - Sheng, Ning; Wang, Yanyan; Xie, Ying; Chen, Sihan; Lu, Jun; Zhang, Zifeng; Li, Mengqiu; Shan, Qun; Wu, Dongmei; Zheng, Guihong; Zheng, Yuanlin; Fan, Shaohua
Abstract: Homo sapiens longevity assurance homolog 2 of yeast LAG1 ( LASS2 ), is a gene isolated from a human liver complementary DNA library. In this study, we found that LASS2 protein level was positively related to International Federation of Gynecology and Obstetrics (FIGO) stage and LASS2‐negative tumors showed significant association with longer disease‐free survival (DFS) and overall survival (OS) in ovarian cancer patients. The heterogeneous expression of LASS2 had been exhibited in diverse ovarian cancer cells. A significantly lower messenger RNA (mRNA) and protein level of LASS2 was seen in 3AO cell compared with those in other types of ovarian cancer cells. Meanwhile, the mRNA and protein levels of LASS2 in ES‐2 and NIH:OVCAR‐3 cells were obviously higher. LASS2 overexpression in 3AO cell could promote migration, invasion, and metastasis abilities in vitro and in vivo, while LASS2 knockdown in ES‐2 and NIH:OVCAR‐3 cells had the opposite effects. The oncogenic capacity of LASS2 in ovarian cancer may be mediated by increased expression of YAP/TAZ. It is indicated that lowering the expression of LASS2 is likely to serve as an unprecedented approach for the treatment of ovarian cancer. Abstract : We found that Homo sapiens longevity assurance homolog 2 of yeast LAG1 (LASS2) expression was positively related to International Federation of Gynecology and Obstetrics (FIGO) stage and LASS2‐negative tumors showed significant association with longer disease‐free survival and overall survival for patients with ovarian cancer. Our research highlighted that LASS2 might serve as an indicator of clinical outcomes for patients with ovarian cancer.